ESENSI AL-MASHLAHAH AL-MURSALAH DALAM TEORI ISTINBAT HUKUM IMAM SYAFI'I - NOORWAHIDAH NOORWAHIDAH (Universitas Islam Negeri Antasari Banjarmasin, 2013)
Imam Muhammad bin Idris asy-SyafiI does not use al-mashlahah al-mursalah as one of the methodologies in making his law. He personally believes that the problem of laws, which do not have nas explicitly in the Holy Al-Quran or hadist, can be solved through ijtihad. The ijtihad is qiyas. Imam Muhammad bin Idris asy-SyafiI divides qiyas into three kinds: qiyas aqwa, qiyas musawi, and qiyas adhaf.His concept of qiyas is elastic and flexible enough to be able to solve the problem of laws in every place and time. In qiyas, there is the essence of al-maslahah al-mursalah